RPG II and RPG III Programming - Tassel Van Dennie (Mcgraw Hill Mitchell, 1986)
A comprehensive presentation of RPG II and RPG III. Preface, RPG Preliminaries, Generating Reports, A First Program, Record and Fields, Editing and Headings, Calculations, Move and Divide and Edit Codes, Advanced Report Writing, Final Totals and RPG Program Logic Style, Final Totals and RPG Program Logic Cycle, Record Identification Codes and Comparing, Programming Techniques, Multiple Input Records and Loops, More on Totals, Input Validating, Tables, Arrays, Sequential File Maintenance, Indexed Sequential Processing, Appendix, Glossary, Index.